Apple Certified Support Professional macOS 11 - Pezet, Don; Memos, Zachary (Packt Publishing, 2024)
The ACSP certification is a vital credential for IT professionals aiming to support macOS environments. This course begins with foundational knowledge on macOS installation, including creating installation media and performing clean installs. You will then delve into initial system configurations, exploring tools like the Migration Assistant and System Preferences to customize your Mac environment. As you progress, the course offers in-depth coverage of user management, encompassing local and iCloud accounts, user account security, and configuring screen time for various users. You will also gain proficiency in managing macOS storage, learning about supported hardware, file systems, encryption, and file permissions. The lessons on network setup and application management further enhance your ability to configure and secure macOS systems. In the final sections, the course focuses on advanced troubleshooting techniques. You will explore methods to diagnose and resolve issues with applications, peripherals, and the macOS boot process. This course also covers backup and recovery solutions using Time Machine, ensuring you can restore systems efficiently. With comprehensive video tutorials and practical exercises, you will be fully prepared to ace the ACSP certification exam and excel in your role as a macOS support professional.
Online resource; title from title details screen (O'Reilly, viewed August 19, 2024)
Keywords: Mac OS; Operating systems (Computers) -- Study guides -- Examinations; Systèmes d'exploitation (Ordinateurs); Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet